Pemberian Hak Nafkah Anak Pasca Perceraian di Pengadilan Agama Jambi - Armevya Sepma; Yenni Erwita (Zaaken: Journal of Civil and Business Law, 2020)
This thesis studies the Granting of Post-Divorce Children's Rights by using 2 decisions as a comparison. Based on Law Number 1 of 1974 concerning Marriage, Law Number 50 of 2009 concerning Religious Courts, Government Regulation of the Republic of Indonesia Number 9 of 1975 Concerning the Implementation of Law Number 1 of 1974 concerning Marriage, Compilation of Islamic Law, and Judges' Courts Jambi religion. The research aims to find out and analyze how the implementation of judges' decisions on children's living rights after divorce in Jambi religious court. Formulation of the problem: (1) How is the granting of post divorce rights in the Jambi Religious Court? (2) What are the factors in the non-implementation of post divorce rights for child divorce in the Jambi Religious Court? Research using empirical juridical legal methods related to the provision of children's living rights after divorce, giving children the right to life is very often, parents ignore their responsibilities so that it does not run in accordance with the contents of the Judges' Decision because the implementation of this ruling lacks concern for the parties to get their rights in accordance with the contents of the Court's decision. The cause is economic factors and communication factors that have broken up after the divorce. While the efforts taken by the mother if the husband does not pay the cost of living then he can submit an execution to the Religious Court. Keywords: Child; Living; Divorce   Abstrak Skripsi ini mengkaji tentang Pemberian Hak Nafkah Anak Pasca Perceraian dengan menggunakan 2 putusan sebagai perbandingan. Berlasndaskan Undang-undang Nomor 1 Tahun 1974 Tentang Perkawinan, Undang-undang Nomor 50 Tahun 2009 Tentang Peradilan Agama, Peraturan Pemerintah Republik Indonesia Nomor 9 Tahun 1975 Tentang Pelaksanaan Undang-undang Nomor 1 Tahun 1974 Tentang Perkawinan, Kompilasi Hukum Islam, serta Putusan Hakim Pengadilan Agama Jambi. Penelitian bertujuan untuk mengetahui dan menganalisis bagaimana pelaksanaan putusan hakim terhadap hak nafkah anak pasca perceraian di pengadilan agama jambi. Rumusan masalah: (1) Bagaimana Pemberian Hak Nafkah Anak Pasca Perceraian di Pengadilan Agama Jambi? (2) Apa Faktor-faktor tidak terlaksananya Pemberian Hak Nafkah Anak Pasca Perceraian di Pengadilan Agama Jambi? Penelitian menggunakan metode hukum yuridis empiris terkait pemberian hak nafkah anak pasca perceraian, pemberian hak nafkah anak sering sekali, orang tua mengabaikan tanggung jawabnya sehingga tidak berjalan sesuai dengan isi Putusan Majelis Hakim dikarenakan Pelaksanaan putusan ini kurang adanya perhatian bagi para pihak untuk mendapatkan hak nya sesuai dengan isi putusan Pengadilan. Penyebabnya adalah faktor ekonomi dan faktor komunikasi yang telah putus setelah terjadinya perceraian. Sedangkan upaya yang ditempuh oleh ibu jika suami tidak membayar biaya nafkah maka ia dapat mengajukan eksekusi ke Pengadilan Agama. Kata Kunci : Nafkah; Anak; Perceraian